How helpful is compensatory financing? - Marie Hulsman-Vejsová (Intereconomics, 1978)
IN INTERECONOMICS, No. 11/12, 1977, Klaus-Peter Treydte discussed the European Communities' “STABEX“ system for export earnings stabilisation. The following contribution compares Stabex with the Compensatory Financing Facility for IMF member countries.
Keywords: 330; Export Earnings